The Effects of High School Basketball Player's Sports Participation Motivation on Achievement Goal Orientation and Achieve-ment Behaviors - Young-Su Jung; Hyunwoo Kang; Seyong Jang (Tehran University of Medical Sciences, 2021)
Background: Although the motivation to set goals and taking steps to achieve them is essential for athletes wishing to progress to a professional level, motives for participating in sports vary depending on personal and physical characteristics. We aimed to investigate the effect of motivation to participate in sports on achievement goal orientation and achievement behavior in high-school basketball players. Methods: The study included 256 female high-school basketball players from Busan, Korea, and was conducted between September and October 2020. The questionnaires obtained data regarding motivation to participate in sports, achievement goal orientation, and achievement behavior. Structural equation modeling was used for data analysis. Results: Motivation to participate in sports exhibited a significant positive correlation with achievement goal orientation (P<0.05). Specifically, motivation related to the development of technical skills and achieving a sense of fulfillment, amusement, and health exerted a positive effect on task-goal orientation. Greater motivation related to technical skill development, attaining a sense of accomplishment, and improving health was associated with greater self-goal orientation. Additionally, achievement goal orientation exerted a significant positive effect on achievement behavior (P<0.05). Conclusion: Given the relative unpopularity of basketball in Korea, it is crucial for players to develop high achievement goal orientation and engage in real efforts to translate such motivation into action. This goal- and achievement-oriented attitude should precede motivation for participating in basketball.